Weaponisation and loss of cultural identity - Nazareth, Samir (2004)
There is a growing relationship between war, weapons trade and natural resources. Usurping natural resources from the local population and even displacing the indigenous people for natural resources has become a way to finance the purchase of weapons for civil war. - Reproduced.
Keywords: Cultural identity